IMPLICATIONS OF MULTIPLE POSITIONS OF THE BOARD OF DIRECTORS ON GOOD CORPORATE GOVERNANCE: RISK AND SUSTAINABILITY PERSPECTIVES - Wahyu Purbo Santoso; Siti Nurhasanah; Pustika Ayuning Puri; Nita Sentia Purba (Jurnal Ekonomi, 2023)
The Board of Directors has a key role in making strategic decisions and carrying out the oversight function within the company. However, the phenomenon of multiple positions, in which one individual holds several positions on the Board of Directors or other corporate boards, can cause a conflict of interest and affect the overall effectiveness of Good Corporate Governance. This study aims to investigate the implications of concurrent positions on the Board of Directors for Good Corporate Governance from a risk and sustainability perspective. This research uses a qualitative approach with descriptive methods. The results of the study show that the practice of holding multiple positions on the board of directors has negative implications for Good Corporate Governance (GCG), including the risk of conflict of interest, lack of transparency, and a decrease in the company's operational efficiency. This threatens accountability, transparency and independence in managing the company. To overcome this impact, companies need to separate positions, increase independent oversight, and increase transparency through clear reporting. Thus, the implementation of good and sustainable GCG can be guaranteed, and the company's reputation as an entity with responsibility and integrity can be strengthened.